EFFECTS OF VIETNAMESE SOPHORA ROOT ON GROWTH, ADHESION, INVASION AND MOTILITY OF MELANOMA CELLS - Zhang, Dongxing; Liu, Shi; Yao, Mingzhu; Liu, Xiong; Lai, Hongtao (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Vietnamese Sophora Root mainly contains active constituents such as alkaloids, and it has anti-tumour, antibacterial, and anti-inflammatory effects. The objective of the paper was to study the effects of Vietnamese Sophora Root on growth, adhesion, invasion and motility of mouse melanoma B16BL6 cells, and to preliminarily explore its mechanism of action. Materials and Methods: MTT assay was used to detect the effect of Vietnamese Sophora Root aqueous extract on B16BL6 cell proliferation. Cell adhesion assay, reconstituted basement membrane invasion assay and chemotactic motility assay were used to observe the effects of Vietnamese Sophora Root aqueous extract on adhesion, invasion and motility of B16BL6 cells. Results: Different concentrations of Vietnamese Sophora Root aqueous extracts had different degrees of inhibitory effects on B16BL6 proliferation. With the decrease of concentration, the proliferation inhibitory effect decreased and even turned to promoting effect. The extract significantly inhibited the adhesion of B16BL6 cells to the basement membrane component LN, and had a significant effect on both the invasive and migratory capacities of B16BL6 cells through the basement membrane. Conclusion: We concluded that the aqueous extract of Vietnamese Sophora Root can inhibit the proliferation of melanoma cells, as well as their adhesion and movement.